Auditing - Robertson, Jack C.; Davis, Frederick G. (Plano, Texas : Business Publications, Inc., 1988)
In our view as textbook authors, we believe students learn auditing by doing audits. Naturally, we believe Auditing provides the foundation of concepts and methods that enables students to understand their activities as financial statement auditors, but there is no real substitute for some "hands on" experience. The Kingston Company case is a practice case-within-a-textbook. The stage is set in Chapter 6 (Beginning an Audit Engagement) with a description of the company's business and organization. Additional information is added to the case in each subsequent chapter, according to the chapter topics. In Chapters 11 and 12, Kingston converts its accounting to a computer system. In Chapters 13 through 18, the text itself describes control systems and account balances with reference to the Kingston Company, providing the background to enable students to apply the chapter concepts in the case assignments at the end of the chapter.
Professional practice -- Auditing theory and practice standards -- Professional ethics -- Legal liability and fraud detection -- Governmental and internal auditing -- Beginning an audit engagement -- Study and evaluation of internal control -- Audit sampling and program planning -- Compliance auditing with attribute sampling -- Account balance auditing with variables sampling -- Planning and controls in a computer environment -- Auditing in a computer environment -- Revenue and collection cycle -- Acquisition and expenditure cycle -- Production and conversion cycle -- Financing and investment cycle -- completing the audit -- Reports by independent auditors -- Reporting on supplementary and unaudited information.
Includes index.
Keywords: AUDITING